Changes in Left atrial strain in patients with aortic stenosis after TAVI. (14th October 2021) - Leo, I; Sabatino, J; Strangio, A; Polimeni, A; Sorrentino, S; Mongiardo, A; Spaccarotella, C A M; Purri, I; De Rosa, S; Indolfi, C
Abstract: Background: Evaluation of left atrial (LA) function is an emerging biomarker of cardiovascular disease (CVD). LA strain by 2D speckle tracking echocardiography (LA strain, LAS) is feasible and reliable, and has been recently associated with adverse long-term outcomes in CVD, including aortic stenosis (AS). Purpose: To evaluate the changes in left atrial strain (LAS) after correction of severe AS with transcatheter aortic valve replacement (TAVR) and assess its prognostic impact. Methods: One hundred consecutive patients with severe symptomatic AS who underwent TAVR at the Magna Graecia University of Catanzaro have been enrolled. Echocardiographic examination before and after TAVR was performed using Vivid E95 system and analysed using the EchoPAC 112.99 workstation (GE Healthcare). Patients underwent clinical follow up visits regularly. The primary study outcome was the difference in ΔLAS (postTAVR-preTAVR) between patients that met the main clinical endpoint (a composite of cardiovascular mortality and heart failure hospitalization) and those not meeting the endpoint. Statistical analyses were performed using JASP (version 0.14.1) and KMWin (version 1.52). Continuous variables were presented as mean and standard deviation and were compared through the unpaired Student's t test or the Mann-Whitney U test in case of a non-normal distribution. Differences between categorical variables were tested with the chi-square test. Multiple logistic regression analysis was performed to identify independent correlates of ΔLAS and to calculate Hazard Ratios (HR) with 95% CI. Kaplan-Meier was used to assess adverse event. Results: During a median follow-up of 31 months, 35 patients (35%) met the composite clinical endpoint. The difference between LAS post-TAVR and LAS pre-TAVR (ΔLAS) was significantly larger in patients who met the combined endpoint (HR=0.76 [0.67–0.86]; p<0.001). Multivariate logistic regression analysis including ΔLAS, EuroSCORE II and left ventricular ejection fraction (LVEF) showed that ΔLAS (HR=0.80, p<0.001) was the only independent predictor of the combined clinical endpoint. Kaplan-Maier analysis showed that patients with a ΔLAS above its median value had a significantly better event-free survival compared to those below the median (p<0.001). Conclusions: A lower reduction in ΔLAS after TAVR was an independent predictor of the primary composite outcome of cardiovascular death and hospitalization for HF. Funding Acknowledgement: Type of funding sources: None.